2000
DOI: 10.1046/j.1464-410x.2000.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Inositol hexakisphosphate in urine: the relationship between oral intake and urinary excretion

Abstract: Objective To study the relationship between the oral intake of inositol hexakisphosphate (InsP 6 , phytic acid, an inhibitor of urinary crystallization) and its urinary excretion, to establish their possible mutual in¯uence. Materials and methods Two groups of male Wistar rats (six animals each) received either; tap water and normal rat food pellets (controls); or a liquid diet in which InsP 6 was absent and which then received gradually increasing amounts of InsP 6 . The urinary levels of InsP 6 were then ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 21 publications
4
44
0
1
Order By: Relevance
“…On the other hand, it is important to emphasize that the attained InsP 6 urinary levels found when InsP 6 was administered orally were almost always inferior to those observed when InsP 6 was topically administered. Thus, maximum InsP 6 urinary levels found when InsP 6 was administered orally through the diet or using specific complements, in no case allowed to attain values superior to 6-7 mg/l InsP 6 , 3) however through topical application urinary values of around 60 mg/l were achieved. This different behaviour of gastrointestinal and skin absorption could be in part explained considering that formation of insoluble no absorbable salts with divalent and trivalent cations and proteins in the gastrointestinal tract is more feasible due to the presence of food or food derivatives.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, it is important to emphasize that the attained InsP 6 urinary levels found when InsP 6 was administered orally were almost always inferior to those observed when InsP 6 was topically administered. Thus, maximum InsP 6 urinary levels found when InsP 6 was administered orally through the diet or using specific complements, in no case allowed to attain values superior to 6-7 mg/l InsP 6 , 3) however through topical application urinary values of around 60 mg/l were achieved. This different behaviour of gastrointestinal and skin absorption could be in part explained considering that formation of insoluble no absorbable salts with divalent and trivalent cations and proteins in the gastrointestinal tract is more feasible due to the presence of food or food derivatives.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it was demonstrated that the levels found in biological fluids (blood, urine, interstitial liquid) and mammalian tissues clearly depended on the dietary intake. [3][4][5] Diverse studies performed by Mellanby demonstrated that a high InsP 6 content in some diets, as sodium salt, reduced calcium absorption and induced rickets. 6) Ever since up to now, several studies have attributed "anti-nutritional" properties to phytate.…”
mentioning
confidence: 99%
“…Urinary excretion of phytate by rats is dependent on dietary supply. Grases et al (25) reported that urinary phytate increased as dietary phytate increased up to a maximum of 20.9 mg/kg body weight. At that intake, about 2% of dietary phytate was absorbed and excreted in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…(182) ); insulin and/or plasma cholesterol and TAG (688 -690) ; lipid levels in liver and serum (691) ; detoxification capacity of liver and levels of GSH transferase and cytochrome P-450 (692) ; immune response (99) ; renal stones (693) ; calcification of cardiovascular system (694) ; dental caries and platelet aggregation, treatment of hypercalciura and kidney stones, and Pb poisoning (218) ; gene expression (695,696) Resistant starch (697) :…”
Section: Appendixmentioning
confidence: 99%